Influence of Gear Helix Angle on Noise of Door Controlled Reducer - Aiqun Xu; Sheng Rao (Jixie chuandong)
Gear noise has become an important index to check the gear processing quality， and it is also a common problem in gear application. In order to effectively solve the noise problem of gears in use， a method which can appropriately increase the helix angle of helical gears to reduce the gear meshing noise is adopted. Taking the first stage motor shaft and helical gears of the door controlled reducer as the analysis object， the model is established and simplified by three-dimensional software， and the sound pressure level of 19°~23° helical angle gear meshing is simulated using the acoustic module in Comsol Multiphysics software； the meshing sound pressure levels of 19°~23° helical angle gears under no-load and loaded conditions are measured with UT353 decibel instrument from close to and 1 m away. The test results show that by improving the helix angle， the reducer noise is optimized by 2~6 dB， and the optimization effect under loaded conditions is better than that under no-load condition. Finally， the stability of mass production of motor shafts and gears is ensured by limiting the use times of cutting tools.